Respuesta :
Multiply it all by ab/1
b + a = abc
subtract a on both sides and subtract abc on both sides
b - abc = -a
divide by -ac on both sides
b = -a/-ac
b = c
I hope that helps
We have given as 1/a+1/b=c. by solving the expression we get b = c.
What is a simplification of an expression?
Usually, simplification involves proceeding with the pending operations in the expression.
Simplification usually involves making the expression simple and easy to use later.
We have given as
1/a+1/b=c
Multiply it all by ab/1
b + a = abc
subtract ABC on both sides
b - abc = -a
divide by -ac into both sides
b = -a/-ac
b = c
Learn more about an expression here:
https://brainly.com/question/1249625
#SPJ2